“Als je je maar jong voelt!” “Oud maar nog jong van hart!” - Marcoen, Alfons (Tijdschrift voor Gerontologie en Geriatrie, 2012)
Bespreking:Weiss,D.,& Lang, F. R. (2012). “They” are old but “I” feelyounger: Age-group dissociation as a self-protective strategyin old age. Psychology and Aging, 27, 153-163.Weiss,D.,& Freund, A. (2012). Still young at heart:Negative age-related information motivates distancingfrom same-aged people. Psychology and Aging, 27, 173-180.